If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -3) = -2x + 18 Reorder the terms: 2(-3 + 3x) = -2x + 18 (-3 * 2 + 3x * 2) = -2x + 18 (-6 + 6x) = -2x + 18 Reorder the terms: -6 + 6x = 18 + -2x Solving -6 + 6x = 18 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 6x + 2x = 18 + -2x + 2x Combine like terms: 6x + 2x = 8x -6 + 8x = 18 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 8x = 18 + 0 -6 + 8x = 18 Add '6' to each side of the equation. -6 + 6 + 8x = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 8x = 18 + 6 8x = 18 + 6 Combine like terms: 18 + 6 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| c^2+11c+24=0 | | 7x+6=12x-3 | | 383n-4.5+16-4=-18+3n-12 | | 5m-2=2m+4 | | 11(x-3)=7x+3 | | 3x+3y=3 | | x^4-5x^2+6=0 | | g+8g-5=-1 | | x^3+7x^2-50x+24=0 | | n-0.3n+2.8=-1.8(n+4) | | 4k+7=5(2-k)+6 | | 3(2k+1)=27 | | n^3+n^2+n=0 | | 26x^2-19x=0 | | 4x-1=2x+13 | | 27m^2-36m+12=0 | | 6x^2+9x-21=0 | | y^3-8y^2+12=0 | | 7x-3=6x+3 | | 7p=6+5p | | 2t-23=-41+4t | | 19n+20n=4 | | x^2-3x-17=0 | | (7t+4)(3t-9)=0 | | 5x^2-20x+10=0 | | -4+12= | | 6x+1=-4 | | 5r-25=-1+8r | | -4+8= | | 6x^2+18=0 | | 10x^2-29x+10=0 | | 20s^2+11sr-3r^2= |